Digital image correlation assisted characterization of Mode I fatigue delamination in composites. (1st December 2020) - Zhu, Man; Gorbatikh, Larissa; Fonteyn, Sander; Van Hemelrijck, Danny; Pyl, Lincy; Carrella-Payan, Delphine; Lomov, Stepan V.
Abstract: A digital image correlation (DIC) based method to characterize the Mode I fatigue delamination onset and propagation in composite laminates is proposed. The characterization is performed using the double cantilever beam test (DCB) under fatigue loading. The DIC is used to analyse the displacement field on the edge of a DCB specimen, from which the crack tip position is determined as a place where opening displacement converges to zero. The method was successfully applied to both the crack onset detection (fatigue onset life) and propagation monitoring under fatigue cycling. The DIC-based method, which relies on the actual crack tip position, gives conservative values for the fatigue onset life in comparison with the compliance based method recommended in the ASTM standard. The DIC assisted method reduces operator and structure dependent errors and shows promise for real-time delamination detection under fatigue loadings.